Les premières géographes universitaires en France : enquête sur les débuts d’une féminisation disciplinaire (1913-1928) - Nicolas Ginsburger (Cybergeo, 2015)
In the first decades of the 20th century, the feminisation of the French academic geography was slow and difficult, but yet effective, particularly during the First World War. It was still the time of pioneer women, in the disciplinary journals as well as in the university. Some names are already well known among these first female geographers, mais this article aims at systematising the inquiry, quantifying and evaluating the process and the reality of the feminine presence in a young but closed scholarly community, where the field work was considered as reserved to men. On that matter, we shall concentrate on the margins of the disciplin, masculin and feminin outsiders and international comparaisons to get a new and more balanced vision of the early years of a quite undervalued evolution.